Method for manufacturing laminated body and method for manufacturing substrate

By stacking temporary adhesive materials on the non-processed surface and support of the silicon substrate, and preheating the substrate and support, the problem of undustration of protection tape in the prior art is solved, efficient bonding between the substrate and the support and durability of subsequent processes is achieved, and the productivity of the thin substrate is improved.

CN111146133BActive Publication Date: 2025-03-11SHIN ETSU CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201911047453.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-11-01
Filing Date
2019-10-30
Publication Date
2025-03-11
Estimated Expiration
2039-10-30

AI Technical Summary

Technical Problem

In the back grinding process of a silicon substrate, the protective tape used is not durable in the subsequent TSV formation and line layer formation processes, and it is difficult to achieve seamless bonding of the substrate and durability of the subsequent processes.

Method used

By stacking temporary adhesive materials on the non-processed surface of the substrate and the support body, the substrate and the support body are preheated to a temperature of 50°C or above and 250°C or below, and bonding is started at different temperature states during bonding, so as to achieve efficient bonding between the substrate and the support body and durability of subsequent processes.

Benefits of technology

This method can achieve seamless bonding between the substrate and the support, and has excellent resistance to thermal processes such as CVD, and has a simple peeling process, which improves the productivity of the thin substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111146133B_ABST
    Figure CN111146133B_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a laminated body, which can easily join a substrate and a support body via a temporary adhesive material, has excellent thermal process resistance, is easy to peel, and can improve the productivity of thin substrates. The manufacturing method joins the non-processed surface of the substrate whose back side is to be processed with the support body via a temporary adhesive material, and is characterized in that it has: a step (a) of stacking a temporary adhesive material on either or both of the non-processed surface of the substrate and the support body; a step (b) of preheating the substrate and the support body before starting to join; a step (c) of joining the substrate and the support body via a temporary adhesive material, in which step (b), the substrate is heated to a temperature of 50°C to 250°C, and the support body is heated to a temperature of 50°C to 250°C and different from that of the substrate, and in step (c), the joining is started in a state where the temperature of the preheated substrate is different from that of the support body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a laminate and a method for producing a substrate. Background Art

[0002] In order to achieve further high density and large capacity, three-dimensional semiconductor mounting is essential. Three-dimensional mounting technology refers to a semiconductor manufacturing technology that thins a single semiconductor chip and further connects it through silicon vias (TSV) and stacks it into multiple layers. In order to achieve three-dimensional mounting, it is necessary to thin the substrate formed with the semiconductor circuit by grinding the non-circuit forming surface (also called the "back side"), and further perform a process of forming an electrode including TSV on the back side.

[0003] In the past, in the back grinding process of silicon substrates, a protective tape was attached to the opposite side of the grinding surface to prevent the substrate from being damaged during grinding. However, this tape uses an organic resin film as a support substrate and has flexibility, but on the other hand, it does not have sufficient strength or heat resistance and is not suitable for the TSV formation process or the back wiring layer formation process.

[0004] Therefore, a system is proposed that can fully withstand the process of back grinding, TSV or back electrode formation by bonding a semiconductor substrate to a support such as silicon or glass via an adhesive layer. At this time, the adhesive layer when bonding the substrate to the support is very important. It is required that the substrate must be bonded to the support without gaps, have sufficient durability to withstand subsequent processes, and further require that the thin substrate can be easily peeled off from the support at the end. Like this, since it is peeled off at the end, in this specification, the adhesive layer is referred to as a temporary adhesive layer, and the material used is referred to as a temporary adhesive material.

[0005] As a known method for manufacturing a laminate using a temporary adhesive layer, a technique is proposed in which a temporary adhesive layer is formed on one or both of a substrate and a support, and the substrate and the support are preheated to the same temperature in a bonding device as required, and then bonded (Patent Documents 1 and 2). These bonding methods have problems when bonding materials with different melt viscosities at the bonding temperature.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2004-64040

[0009] Patent Document 2: Japanese Patent No. 6059631 Summary of the invention

[0010] Technical Problems to be Solved by the Invention

[0011] The present invention is completed in view of the above-mentioned problems, and its purpose is to provide a method for manufacturing a laminate, which can easily join a substrate and a support body via a temporary adhesive material, has excellent resistance to thermal processes such as CVD (chemical vapor deposition), is easy to peel off, and can improve the productivity of thin substrates.

[0012] Technical means to solve technical problems

[0013] In order to achieve the above-mentioned purpose, the present invention provides a method for manufacturing a stacked body, which is a method for manufacturing a stacked body in which a non-processed surface of a substrate to be processed on the back side (the non-back surface of the substrate) is joined to a support body via a temporary adhesive material, characterized in that it comprises: a step (a) of stacking the temporary adhesive material on either or both of the non-processed surface of the substrate and the support body; a step (b) of preheating the substrate and the support body before the start of bonding; a step (c) of joining the substrate and the support body via the temporary adhesive material, in which, in the step (b), the substrate is heated to a temperature of not less than 50°C and not more than 250°C, and the support body is heated to a temperature of not less than 50°C and not more than 250°C and different from that of the substrate, and at the same time, in the step (c), the bonding is started in a state where the temperature of the preheated substrate is different from the temperature of the support body.

[0014] The method for producing a laminate of the present invention can easily bond a substrate and a support via a temporary adhesive material, has excellent resistance to a thermal process such as CVD (chemical vapor deposition), is easy to peel, and can improve productivity of thin substrates.

[0015] At this time, in the step (c), it is preferred that bonding is started in a state where the temperature of the substrate and the temperature of the support differ by 10° C. or more.

[0016] The method for producing a laminate under such temperature conditions is preferred because the laminate has excellent embedding properties into a concavo-convex substrate.

[0017] In addition, in the present invention, as the temporary adhesive material, it is preferred to use a temporary adhesive material having at least two layers, a first temporary adhesive material layer (A) located on the substrate side and a second temporary adhesive material layer (B) closer to the support body side than the first temporary adhesive material layer (A).

[0018] In the case of such a temporary adhesive material, temporary adhesive material layers having different properties such as melt viscosity can be selected as needed.

[0019] At this time, it is preferred to use a temporary adhesive material having a melt viscosity ratio α / β of the first temporary adhesive material layer (A) and the second temporary adhesive material layer (B) of 10 or less as a melt viscosity ratio at 25°C and 100 or more as a minimum melt viscosity ratio at 100°C to 200°C.

[0020] If the temporary adhesive material has such a melt viscosity ratio, the bonding process can be performed in a short time, which is preferable.

[0021] Furthermore, in the present invention, it is preferred that in the step (a), the first temporary adhesive material layer (A) and the second temporary adhesive material layer (B) are formed adjacent to each other and the temporary adhesive materials are laminated.

[0022] In this case, it is preferable to use a temporary adhesive material in which the second temporary adhesive material layer (B) is composed of a thermosetting resin and the elastic modulus of a cured film obtained by curing the thermosetting resin is 50 MPa to 1 GPa at 25°C as measured by dynamic viscoelasticity measurement.

[0023] When the cured film is the second temporary adhesive material layer (B) having such an elastic modulus, the substrate is preferably not warped during temporary fixing, particularly after grinding the substrate.

[0024] In addition, in the present invention, it is preferred that the second temporary adhesive material layer (B) is formed of a thermosetting resin composition, and the thermosetting resin composition contains 0.1 to 50 parts by weight of any one or more selected from the group consisting of amino condensates modified with formalin or formalin-alcohol, melamine resins, urea-formaldehyde resins, phenolic compounds having an average of more than 2 methylol or alkoxymethylol groups in one molecule, and epoxy compounds having an average of more than 2 epoxy groups in one molecule as a crosslinking agent, relative to 100 parts by weight of a siloxane bond-containing polymer having a repeating unit represented by the following general formula (1) and a weight-average molecular weight of 3,000 to 500,000.

[0025] [Chemical formula 1]

[0026]

[0027] In the formula, R 1 ~R 4 represents a monovalent hydrocarbon group having 1 to 8 carbon atoms which may be the same or different. In addition, m is an integer of 1 to 100, B is a positive number, and A is 0 or a positive number. Wherein, A+B=1. X is a divalent organic group represented by the following general formula (2).

[0028] [Chemical formula 2]

[0029]

[0030] In the formula, Z is a divalent organic group selected from any one of the following groups, and N is 0 or 1. 5 , R 6 Each of them is an alkyl group or an alkoxy group having 1 to 4 carbon atoms, and they may be the same or different from each other. k is any one of 0, 1, and 2.

[0031] [Chemical formula 3]

[0032]

[0033] Such a second temporary adhesive material layer (B) is preferred because it has better heat resistance.

[0034] In addition, in the present invention, it is preferred that the second temporary adhesive material layer (B) is formed of a thermosetting resin composition, wherein the thermosetting resin composition contains 0.1 to 50 parts by weight of any one or more selected from a phenol compound having an average of two or more phenolic hydroxyl groups in one molecule and an epoxy compound having an average of two or more epoxy groups in one molecule as a crosslinking agent, relative to 100 parts by weight of a siloxane bond-containing polymer having a repeating unit represented by the following general formula (3) and a weight-average molecular weight of 3,000 to 500,000.

[0035] [Chemical formula 4]

[0036]

[0037] In the formula, R 7 ~R 10 represents a monovalent hydrocarbon group having 1 to 8 carbon atoms which may be the same or different. In addition, n is an integer of 1 to 100, D is a positive number, and C is 0 or a positive number. Wherein, C+D=1. Furthermore, Y is a divalent organic group represented by the following general formula (4).

[0038] [Chemical formula 5]

[0039]

[0040] In the formula, V is a divalent organic group selected from any one of the following groups, and p is 0 or 1. 11 , R 12 Each of them is an alkyl group or an alkoxy group having 1 to 4 carbon atoms, and they may be the same or different from each other. h is any one of 0, 1, and 2.

[0041] [Chemical formula 6]

[0042]

[0043] Such a second temporary adhesive material layer (B) is preferred because it has better heat resistance.

[0044] In addition, the present invention provides a method for manufacturing a substrate, wherein, after a laminate is obtained by the above-mentioned method for manufacturing a laminate, a step (d) of processing the back side of the substrate is performed, and then after further removing the support body and the temporary adhesive material from the laminate, there is a step (e) of cleaning the substrate, and in the step (e), the contact angle of water on the surface of the cleaned substrate from which the support body is removed is set to less than 30°.

[0045] According to such a method for manufacturing a substrate, a substrate can be manufactured without causing a problem due to a temporary adhesive material in a subsequent process, and a thin substrate having a through-hole electrode structure or a bump connection structure can be manufactured easily.

[0046] Effects of the Invention

[0047] As described above, the method for manufacturing a laminate of the present invention can easily manufacture a laminate using materials with different melt viscosities. By making it possible to use materials with different melt viscosities, a laminate can be manufactured using various materials. In addition, the generation of defects such as voids that accompany the manufacture of the laminate can be prevented in advance, and the productivity of the thin substrate can be greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a diagram showing the structure of an example of a laminate obtained by the method for producing a laminate of the present invention.

[0049] Figure 2 This is a structural diagram showing an example of heating the substrate and the support body before bonding according to the present invention.

[0050] Figure 3 This is a structural diagram showing an example of a laminated body immediately after bonding according to the present invention.

[0051] Description of Reference Numerals

[0052] 1: substrate; 2: temporary adhesive material; (A): first temporary adhesive material layer; (B): second temporary adhesive material layer; 3: support body; 4: substrate setting plate; 5: support body setting plate. DETAILED DESCRIPTION

[0053] As described above, there is a need for a temporary adhesive material for substrate processing that is easy to temporarily bond, has a fast formation speed of the temporary adhesive material on a substrate or a support, has excellent dimensional stability, has excellent resistance to substrate thermal processes such as CVD, is easy to peel off, and can improve the productivity of thin substrates.

[0054] In order to achieve the above-mentioned purpose, the inventors of the present application have conducted careful research and found that by preheating the substrate and the support body before the start of bonding, heating the substrate to a temperature of not less than 50°C and not more than 250°C, heating the support body to a temperature of not less than 50°C and not more than 250°C and different from that of the substrate, and simultaneously in the process of bonding the substrate and the support body via a temporary adhesive material, starting the bonding in a state where the temperature of the preheated substrate is different from the temperature of the support body, a thin substrate with a through-hole electrode structure or a bump connection structure can be simply manufactured, thereby completing the present invention.

[0055] That is, the present invention is a method for manufacturing a laminate, which is a method for manufacturing a laminate in which a non-processed surface of a substrate to be processed on the back side is joined to a support body via a temporary adhesive material, and is characterized in that it has: a step (a) of stacking the temporary adhesive material on either or both of the non-processed surface of the substrate and the support body; a step (b) of preheating the substrate and the support body before starting to join; and a step (c) of joining the substrate and the support body via the temporary adhesive material, in which, in the step (b), the substrate is heated to a temperature of not less than 50°C and not more than 250°C, and the support body is heated to a temperature of not less than 50°C and not more than 250°C and different from that of the substrate, and at the same time, in the step (c), joining is started in a state where the temperature of the preheated substrate is different from the temperature of the support body.

[0056] If it is such a manufacturing method of the laminate of the present invention, it is possible to prepare a laminate without defects such as voids when bonding materials with different melt viscosities. Therefore, the present invention can easily obtain a laminate formed by bonding the non-processed surface of the substrate to be processed on the back side with a support body via a temporary adhesive material.

[0057] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto.

[0058] [Laminated body]

[0059] Figure 1 FIG. 2 is a structural diagram showing an example of a laminate obtained by the method for producing a laminate of the present invention. Figure 1 As shown, the laminate is formed by bonding a substrate 1 and a support 3 via a temporary adhesive material 2 .

[0060] The substrate 1 is, for example, a substrate having one surface as a circuit-forming surface and another surface (back surface) to be processed as a non-circuit-forming surface. The substrate applicable to the present invention is generally a semiconductor substrate. Examples of the semiconductor substrate include a disc-shaped wafer or a square substrate. Examples of wafers include not only silicon wafers but also germanium wafers, gallium-arsenic wafers, gallium-phosphorus wafers, gallium-arsenic-aluminum wafers, and the like. The thickness of the substrate is not particularly limited, and is typically 600 to 800 μm, more typically 625 to 775 μm.

[0061] The support 3 is not particularly limited, and a substrate such as a silicon wafer, a glass plate, or a quartz wafer can be used. In the present invention, the temporary adhesive material is not necessarily irradiated with radiation energy rays through the support, and the support may not be light-transmissive.

[0062] Temporary adhesive material 2 is an adhesive layer when substrate is joined to a support body, as long as substrate can be joined to a support body without gap, has sufficient tolerance to withstand subsequent processes, and further can be easily peeled off from a thin substrate from a support body at the end, then there is no particular limitation. In addition, the temporary adhesive material 2 used in the present invention can be a single layer, or it can be composed of a plurality of layers. Hereinafter, each layer constituting the temporary adhesive material in this way will also be referred to as a temporary adhesive material layer. As a temporary adhesive material 2 for the manufacture method of the laminate of the present invention, it is preferred that at least a first temporary adhesive material layer (A) is provided on the substrate side and a second temporary adhesive material layer (B) closer to the support body side than the first temporary adhesive material layer (A) is provided.

[0063] The laminated body when the temporary adhesive material 2 is composed of the first temporary adhesive material layer (A) and the second temporary adhesive material layer (B) is shown in FIG. Figure 1 .

[0064] Below, with Figure 1 The manufacturing method of the laminate shown in the present invention is described with the focus on the temporary adhesive material used in the manufacturing method of the laminate of the present invention, but the present invention is not limited to this. In addition, for the temporary adhesive material used in the manufacturing method of the laminate of the present invention, the temporary adhesive material having the first temporary adhesive material layer (A) and the second temporary adhesive material layer (B) is described with the focus on the temporary adhesive material, but it can only have any one of (A) and (B), and can also have a layer other than (A) and (B).

[0065] [Method for producing laminated body]

[0066] The method for manufacturing a laminate of the present invention is a method for manufacturing a laminate by joining a non-processed surface (the surface of the substrate that is not the back side: the surface on which the semiconductor circuit is formed) of a substrate (a substrate having a semiconductor circuit, etc.) to be processed on the back side with a support body via a temporary adhesive material, which has the following steps.

[0067] Step (a): a step of laminating a temporary adhesive material on one or both of the non-processed surface of the substrate and the support

[0068] Step (b): Preheating the substrate and the support before bonding

[0069] Step (c): a step of bonding the substrate and the support body via a temporary adhesive material

[0070] In the present invention, in the step (b), the substrate is heated to a temperature of 50°C to 250°C, and the support is heated to a temperature of 50°C to 250°C and different from that of the substrate, and at the same time in the step (c), the bonding is started in a state where the temperature of the pre-heated substrate is different from that of the support. The heating time is not particularly limited, and is preferably about 30 seconds to 5 minutes. The temporary adhesive material is heated together with the substrate and / or support on which it is stacked.

[0071] In the present invention, before the start of bonding is defined as a state from when the substrate and the support are set at a predetermined position such as in a chamber in a bonding apparatus to when the substrate and the support are brought into contact with each other.

[0072] Figure 2 An example of heating the substrate and the support before bonding of the present invention is shown. Figure 2 As shown, a substrate 1 is placed on a substrate placement plate 4 disposed in a bonding device, and a support 3 preliminarily laminated with a temporary adhesive material 2 is placed on a support placement plate 5. Each plate 4, 5 has an arbitrary heating means, thereby being able to heat the substrate side and the support side to arbitrary temperatures, respectively.

[0073] In the method for manufacturing a laminate of the present invention, in step (b), the substrate temperature is preheated to a temperature of 50°C to 250°C, and the support temperature is preheated to a temperature of 50°C to 250°C, and simultaneously in step (c), bonding is started simultaneously with the substrate temperature and the support temperature being different.

[0074] In addition, the temperature difference between the substrate temperature and the support body temperature can be appropriately set, but it is preferred to start bonding in a state where the difference is 10°C or more. The upper limit of the temperature difference is preferably set to a difference of 100°C or less, and the lower limit is not particularly limited, but is more preferably set to a difference of 20°C or more. Furthermore, it is desirable to set the temperature of the substrate to a temperature higher than the temperature of the support body.

[0075] According to such a bonding method, the occurrence of defects such as voids originating from the bonding step can be sufficiently suppressed.

[0076] -Step (a)-

[0077] Step (a) is a step of laminating a temporary adhesive material on any one or both of the non-processed surface (not the back surface) of the substrate and the support. Below, the step of laminating a temporary adhesive material on the support is centered on the description, but a temporary adhesive material can also be laminated on the substrate side.

[0078] For example, the temporary adhesive material can be laminated (formed) by applying the resin composition solution to any one or both of the non-processed surface of the substrate and the support (hereinafter, also referred to as "support, etc.") by a known method such as spin coating, roll coating, etc. At this time, after spin coating, the solvent is volatilized in advance at a temperature of 80 to 200° C., preferably at a temperature of 100 to 180° C., according to the volatilization conditions of the solvent, and then provided for use.

[0079] When stacking the temporary adhesive material consisting of more than 2 layers, each layer can be formed on the substrate and the support, respectively, or multiple layers can be formed only on the substrate or only on the support. When multiple layers are formed, after forming the first layer, the same method can be used again to form the second layer in a manner adjacent to the first layer. Each layer can be formed by the above method.

[0080] Alternatively, the temporary adhesive material may be laminated on a support or the like by laminating a temporary adhesive material previously formed in a film form on a release substrate.

[0081] As a device for laminating the temporary adhesive material on a support, a commercially available device can be used. When laminating by spin coating, the coating device can be, for example, XBS300 of SUSS Company, and when laminating by lamination, a vacuum laminator can be cited, for example, TEAM-300 of Takatori Corporation.

[0082] -Step (b)-

[0083] Step (b) is a step of preheating the substrate and the support before starting the bonding. This step can be performed in a bonding device. In this case, the heating means is built into the bonding device, and a heater is built into the plate (chamber) where the substrate and the support are set. In addition, there is no particular problem as long as the heater is a well-known heating device. The substrate is heated to a temperature of 50°C to 250°C, and the support is heated to a temperature of 50°C to 250°C and different from that of the substrate.

[0084] The heating is preferably performed at a temperature difference of 10° C. or more, more preferably at a temperature difference of 20° C. or more.

[0085] -Step (c)-

[0086] Step (c) is a step of bonding the substrate and the support body via a temporary adhesive material. Preferably, the bonding and bonding are performed under reduced pressure. For example, the substrate is uniformly pressed and bonded under vacuum (under reduced pressure; pressure is 1 Pa or less) at the temperature conditions for heating in step (b), thereby forming a laminated body in which the substrate and the support body are bonded via a temporary adhesive material. At this time, the pressing time is 10 seconds to 10 minutes, preferably 30 seconds to 5 minutes.

[0087] For example, Figure 2 As shown, a substrate 1 is placed on a substrate placement plate 4, and a support 3 on which a temporary adhesive material 2 is laminated is placed on a support placement plate 5, and then the substrate side and the support side are heated to different predetermined temperatures, respectively. Figure 3 As shown, the substrate 1 is uniformly pressed and bonded to the side of the support 3 on which the temporary adhesive material 2 is laminated under reduced pressure.

[0088] When the substrate is a wafer, the substrate bonding apparatus may be a commercially available wafer bonding apparatus such as EVG520IS and 850TB manufactured by EVG and XBS300 manufactured by SUSS.

[0089] [Temporary adhesive material layer]

[0090] The temporary adhesive material used in the present invention can be a monolayer, and can also be composed of multiple layers. As a temporary adhesive material, preferably use at least a temporary adhesive material having a first temporary adhesive material layer (A) positioned at substrate side and more than 2 layers of the second temporary adhesive material layer (B) closer to support body side than this first temporary adhesive material layer (A). In addition, further, also can have the 3rd temporary adhesive material layer (C) or other functional layers.

[0091] At this time, it is preferred to use a temporary adhesive material having a melt viscosity ratio α / β of 10 or less as a melt viscosity ratio at 25°C and a minimum melt viscosity ratio at 100°C to 200°C of 100 or more. The melt viscosity ratio α / β (25°C) at 25°C is more preferably 0.05 to 5, and more preferably 0.05 to 1. In addition, the minimum melt viscosity ratio at 100°C to 200°C is more preferably 100 to 1000, and more preferably 120 to 500.

[0092] If the temporary adhesive material has such a melt viscosity ratio, the bonding process can be performed in a short time, so it is preferred. In addition, if it is a temporary adhesive material with such a melt viscosity ratio, the temporary adhesive material will not adhere to the substrate periphery during bonding, so it is preferred.

[0093] Hereinafter, the temporary adhesive material (temporary adhesive material layer) used in the method for producing the laminated body of the present invention will be described in detail, but the temporary adhesive material that can be used is not limited thereto.

[0094] -First temporary adhesive material layer (A)-

[0095] The first temporary adhesive material layer (A) is a layer located at the substrate side in the temporary adhesive material layer constituting the temporary adhesive material. Its material is not particularly limited, and from the applicability of the substrate with step difference etc., it is suitable to use a thermoplastic resin with good embeddability. Below, the example that the first temporary adhesive material layer (A) is constituted by a thermoplastic resin is described in detail, but the temporary adhesive material used in the manufacture method of laminated body of the present invention is not limited thereto.

[0096] The first temporary adhesive material layer (A) is preferably a thermoplastic resin that does not contain organic polysiloxane and has a glass transition temperature of about -80 to 150°C, examples of which include olefin thermoplastic elastomers, polybutadiene thermoplastic elastomers, styrene thermoplastic elastomers, styrene-butadiene thermoplastic elastomers, styrene-polyolefin thermoplastic elastomers, and hydrogenated polystyrene elastomers with excellent heat resistance are particularly suitable.

[0097] As such thermoplastic resins, commercial products can be used, and specific examples include Tuftec (Asahi Kasei Corporation.), ESPOLEX SB Series (Sumitomo Chemical Co., Ltd.), RABALON (Mitsubishi Chemical Corporation), SEPTON (KURARAY CO., LTD), DYNARON (JSR CORPORATION), etc. In addition, cycloolefin polymers represented by ZEONEX (ZEON CORPORATION) and cycloolefin copolymers represented by TOPAS (Polyplastics Co., Ltd.) can be mentioned.

[0098] As described above, the thermoplastic resin of the first temporary adhesive material layer (A) is preferably a thermoplastic elastomer. Alternatively, two or more resins may be used simultaneously.

[0099] According to such a first temporary adhesive material layer (A), after the thin substrate is produced, the temporary adhesive material can be more easily peeled off or washed from the substrate, so that the thin substrate that is easily broken can be handled more easily.

[0100] The above-mentioned thermoplastic resin layer composition can be dissolved in a solvent and made into (A) layer solution, thereby used to form a temporary adhesive material layer. As a solvent, hydrocarbon solvents can be listed, and nonane, p-menane, pinene, isooctane, mesitylene etc. can be preferably listed, and according to its coating property, nonane, p-menane, isooctane, mesitylene are more preferably nonane, p-menane, isooctane, mesitylene. Further, it is also possible to filter as required. Then, preferably use forward roll coater (forward roll coater), reverse roll coater (reverseroll coater), comma coater (comma coater), die coater (die coater), lip coater (lipcoater), gravure coater, dip coater, air knife coater, capillary coater (capillary coater), convex rising type (raising and rising (R&R)) coater, blade coater, rod coater, applicator (applicator), extrusion molding machine etc. to be coated on the demoulding substrate. Then, the first temporary adhesive material layer (A) is formed by removing the solvent on the release substrate coated with the (A) layer solution in-line.

[0101] At this time, the film thickness formed is not limited, and it is suitable to be formed into a film thickness of 0.5 to 80 μm, and more preferably formed into a film thickness of 0.5 to 50 μm. In addition, in the thermoplastic resin, an antioxidant can be added for the purpose of improving its heat resistance, or a surfactant can be added to improve the coating property. As a specific example of an antioxidant, 2,5-di-tert-butylphenol and the like are suitable. As an example of a surfactant, a fluorosilicone surfactant X-70-1102 (manufactured by Shin-Etsu Chemical Co., Ltd.) and the like are suitable.

[0102] -Second temporary adhesive material layer (B)-

[0103] The second temporary adhesive material layer (B) is a temporary adhesive material layer that is closer to the support body side than the above-mentioned first temporary adhesive material layer (A) in the temporary adhesive material layer constituting the temporary adhesive material. Its material is not particularly limited, and is preferably composed of a thermosetting resin, and more preferably composed of an organosilicon resin. It is particularly preferred that the thermosetting siloxane-modified polymer (containing siloxane bond polymer) represented by the following general formula (1) and / or (3) is formed as a thermosetting resin composition of a main component. Further, the resin combination can contain a crosslinking agent or a curing catalyst as required.

[0104] In addition, the second temporary adhesive material layer (B) can simultaneously use a polymer represented by the following general formula (1) and a polymer represented by the following general formula (3). The ratio (mass ratio) at this time is preferably (1): (3) = 0.1: 99.9 to 99.9: 0.1, and more preferably (1): (3) = 1: 99 to 99: 1.

[0105] <Polymer of general formula (1) (phenolic siloxane polymer)>

[0106] A siloxane bond-containing polymer having a repeating unit represented by the following general formula (1) and having a polystyrene-equivalent weight average molecular weight of 3,000 to 500,000, preferably 10,000 to 100,000, as determined by gel permeation chromatography (GPC).

[0107] [Chemical formula 7]

[0108]

[0109] In the formula, R 1 ~R 4 represents a monovalent hydrocarbon group having 1 to 8 carbon atoms which may be the same or different. In addition, m is an integer of 1 to 100, B is a positive number, and A is 0 or a positive number. X is a divalent organic group represented by the following general formula (2). A+B=1. In addition, preferably A is 0 to 0.9 and B is 0.1 to 1. In addition, when A is greater than 0, preferably A is 0.1 to 0.7 and B is 0.3 to 0.9.

[0110] [Chemical formula 8]

[0111]

[0112] In the formula, Z is a divalent organic group selected from any one of the following groups, and N is 0 or 1. 5 , R 6 Each of them is an alkyl group or an alkoxy group having 1 to 4 carbon atoms, and they may be the same or different from each other. k is any one of 0, 1, and 2.

[0113] [Chemical formula 9]

[0114]

[0115] At this time, as R 1 ~R 4 Specific examples include methyl, ethyl, phenyl, etc., and m is an integer of 1 to 100, preferably 3 to 60, and more preferably 8 to 40. In addition, B / A is preferably greater than 0 and less than 20, and particularly preferably 0.5 to 5.

[0116] <Polymer of general formula (3) (epoxy-modified siloxane polymer)>

[0117] A siloxane bond-containing polymer having a repeating unit represented by the following general formula (3) and having a polystyrene-equivalent weight average molecular weight of 3,000 to 500,000 as determined by GPC.

[0118] [Chemical formula 10]

[0119]

[0120] In the formula, R 7 ~R 10 represents a monovalent hydrocarbon group having 1 to 8 carbon atoms which may be the same or different. In addition, n is an integer of 1 to 100, D is a positive number, and C is 0 or a positive number. Further, Y is a divalent organic group represented by the following general formula (4). C+D=1. In addition, preferably, C is 0 to 0.9 and D is 0.1 to 1. Furthermore, when C is greater than 0, preferably, C is 0.1 to 0.7 and D is 0.3 to 0.9.

[0121] [Chemical formula 11]

[0122]

[0123] In the formula, V is a divalent organic group selected from any one of the following groups, and p is 0 or 1. 11 , R 12 Each of them is an alkyl group or an alkoxy group having 1 to 4 carbon atoms, and they may be the same or different from each other. h is any one of 0, 1, and 2.

[0124] [Chemical formula 12]

[0125]

[0126] At this time, as R 7 ~R 10 Specific examples include the following: 1 ~R 4 The same groups as those exemplified in . In addition, n is an integer of 1 to 100, preferably 3 to 60, more preferably 8 to 40. In addition, D / C is preferably greater than 0 and less than 20, and particularly preferably 0.5 to 5.

[0127] <Cross-linking agent>

[0128] In order to thermally cure the thermosetting composition having the thermosetting siloxane-modified polymer of the general formula (1) and / or (3) as the main component, when the main component is the phenolic siloxane polymer of the general formula (1), it can contain any one or more crosslinking agents selected from the group consisting of amino condensates modified with formalin or formalin-alcohol, melamine resins, urea-formaldehyde resins, phenolic compounds having an average of more than two methylol or alkoxymethylol groups in one molecule, and epoxy compounds having an average of more than two epoxy groups in one molecule.

[0129] Here, as amino condensates, melamine resins, and urea-formaldehyde resins modified by formalin or formalin-alcohol, the following materials can be listed. For example, the melamine resin (condensates) modified by formalin or formalin-alcohol can be obtained by the following method: according to a known method, a modified melamine monomer (for example trimethoxymethyl monomethylol melamine) or its polymer (for example oligomers such as dimers and trimers) is subjected to addition polycondensation with formaldehyde until the desired molecular weight is reached. In addition, they can be used one or two or more in combination.

[0130] In addition, the preparation of formalin or formalin-alcohol modified urea-formaldehyde resin (condensation product) can be carried out in the following manner: according to known method, formalin is utilized to carry out hydroxymethylation and modification of the urea condensation product of required molecular weight, or alcohol is further utilized to carry out alkoxylation and modification.As the specific example of formalin or formalin-alcohol modified urea-formaldehyde resin, for example, methoxymethylation urea condensation product, ethoxyethylation urea condensation product, propoxymethylation urea condensation product etc. can be listed.In addition, they can use one or use two or more in combination.

[0131] Examples of phenol compounds having an average of two or more methylol groups or alkoxymethylol groups in one molecule include (2-hydroxy-5-methyl)-1,3-benzenedimethanol and 2,2',6,6'-tetramethoxymethylbisphenol A. These phenol compounds can be used alone or in combination of two or more.

[0132] On the other hand, when the main component is an epoxy-modified siloxane polymer (siloxane bond-containing polymer) of the general formula (3), it can contain as a crosslinking agent any one or more selected from a phenol compound having an average of two or more phenolic hydroxyl groups in one molecule and an epoxy compound having an average of two or more epoxy groups in one molecule.

[0133] Here, the epoxy compound having a multifunctional epoxy group used in the general formula (1) and / or (3) is not particularly limited and may contain a difunctional, trifunctional, or tetrafunctional or higher multifunctional epoxy resin, for example, EOCN-1020, EOCN-102S, XD-1000, NC-2000-L, EPPN-201, GAN, NC6000 manufactured by Nippon Kayaku Co., Ltd., or a crosslinking agent such as the following formula.

[0134] [Chemical formula 13]

[0135]

[0136] When the main component is the epoxy-modified siloxane polymer of the above-mentioned general formula (3), specific examples of the phenol compound having an average of more than 2 phenolic hydroxyl groups in one molecule as a cross-linking agent include meta- and para-cresol novolac resins, for example, EP-6030G manufactured by Asahi Organic Chemicals Industry Co., Ltd.; or trifunctional phenol compounds, for example, Tris-P-PA manufactured by Honshu Chemical Industry Co., Ltd.; or tetrafunctional phenol compounds, for example, TEP-TPA manufactured by Asahi Organic Chemicals Industry Co., Ltd., etc.

[0137] The amount of the crosslinking agent added can be set to 0.1 to 50 parts by mass, preferably 0.1 to 30 parts by mass, and more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the thermosetting polymer (polymer containing siloxane bonds) of the above-mentioned general formula (1) or formula (3). It can also be mixed and blended with two or more kinds of the crosslinking agent.

[0138] Furthermore, 10 parts by mass or less of a curing catalyst such as an acid anhydride may be contained based on 100 parts by mass of the thermosetting polymer.

[0139] [Other ingredients]

[0140] The thermosetting resin layer composition can be dissolved in a solvent to prepare a (B) layer solution, which is used to form a temporary adhesive material layer. Examples of the solvent include ketones such as cyclohexanone, cyclopentanone, and methyl-2-n-pentyl ketone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, propylene glycol monotert-butyl ether acetate, and γ-butyrolactone, and the like. One of these solvents can be used alone, or two or more thereof can be used simultaneously. Furthermore, filtration may be performed as necessary. Then, the (B) layer is formed by applying the (A) layer formed on the release substrate in the same manner as the (A) layer, and removing the solvent.

[0141] In order to further improve the heat resistance, 50 parts by mass or less of a known antioxidant, filler such as silica, etc. may be added to 100 parts by mass of the thermosetting polymer. Furthermore, a surfactant may be added to improve the coating uniformity.

[0142] Specific examples of the antioxidant that can be added to the second temporary adhesive material layer (B) include hindered phenol compounds such as pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate) (trade name: Adekastab AO-60).

[0143] At this time, the thickness of the film formed is not particularly limited, but is preferably 5 to 150 μm, and more preferably 10 to 120 μm. If the film thickness is 5 μm or more, it can fully withstand the grinding process of substrate thinning, and if it is 150 μm or less, the resin will not deform during the heat treatment process such as the TSV formation process, and it can withstand actual use, so it is preferred.

[0144] -Third temporary adhesive material layer (C)-

[0145] The temporary adhesive material used in the method for producing the laminate of the present invention may further contain a third temporary adhesive material layer as needed. When the third temporary adhesive material layer is used, a composition (thermosetting silicone polymer composition) containing the following components (c1), (c2), and (c3) is particularly preferred.

[0146] (c1) Organopolysiloxane having an alkenyl group in the molecule: 100 parts by mass

[0147] (c2) an organohydrogenpolysiloxane containing two or more hydrogen atoms (Si-H groups) bonded to silicon atoms in one molecule: the molar ratio of the Si-H groups in the component (c2) to the alkenyl groups in the component (c1) is 0.3 to 15

[0148] (c3) Platinum catalyst: more than 0 parts by mass and not more than 0.5 parts by mass as an effective component (in terms of mass)

[0149] Hereinafter, each component will be described.

[0150] <(c1) Ingredient>

[0151] The component (c1) is an organopolysiloxane having an alkenyl group in the molecule. The component (c1) is preferably a linear or branched organopolysiloxane containing 0.3 to 10 mol% of alkenyl groups in one molecule relative to the molar number of Si (molar number of alkenyl groups / molar number of Si). The organopolysiloxane containing 0.6 to 9 mol% of alkenyl groups relative to the molar number of Si is particularly preferred.

[0152] Specific examples of such organopolysiloxane include compounds represented by the following formula (5) and / or (6).

[0153] R 13 (3-a) X 1 a SiO-(R 13 X 1 SiO) l -(R 13 2SiO) r -SiR 13 (3-a) X 1 a (5)

[0154] R 13 2(HO)SiO-(R 13 X 1 SiO) l+2 -(R 13 2SiO) r -SiR 13 2(OH) (6)

[0155] In the formula, R 13 are each independently a monovalent hydrocarbon group having no aliphatic unsaturated bond, X 1Each is independently a monovalent organic group containing an alkenyl group, and a is an integer of 0 to 3. In formula (5), 2a+1 is a number such that the alkenyl content in one molecule is 0.3 to 10 mol%. In formula (6), l+2 is a number such that the alkenyl content in one molecule is 0.3 to 10 mol%. l is a positive number of 0 or 500 or less, and r is a positive number of 1 to 10,000.

[0156] In the above formula, R 13 , preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms and having no aliphatic unsaturated bonds, examples of which include alkyl groups such as methyl, ethyl, propyl, and butyl; cycloalkyl groups such as cyclohexyl; aryl groups such as phenyl and tolyl, and particularly preferably alkyl groups such as methyl or phenyl.

[0157] As X 1 The monovalent organic group containing an alkenyl group is preferably an organic group having 2 to 10 carbon atoms, and examples thereof include alkenyl groups such as vinyl, allyl, hexenyl, and octenyl; (meth)acryloylalkyl groups such as acryloylpropyl, acryloylmethyl, and methacryloylpropyl; (meth)acryloyloxyalkyl groups such as acryloyloxypropyl, acryloyloxymethyl, methacryloyloxypropyl, and methacryloyloxymethyl; and monovalent hydrocarbon groups containing an alkenyl group such as cyclohexenylethyl and vinyloxypropyl. Vinyl is particularly preferred in industry.

[0158] In the above general formula (5), a is an integer of 0 to 3. If a is 1 to 3, the molecular chain end is capped with an alkenyl group. Therefore, the molecular chain end alkenyl group with good reactivity can complete the reaction in a short time, so it is preferred. Furthermore, in terms of cost, a=1 is industrially preferred. The alkenyl-containing organopolysiloxane is preferably in an oily or rubbery state. The alkenyl-containing organopolysiloxane may be linear or branched. In addition, two or more components (c1) may be used simultaneously.

[0159] The component (c1) preferably has a number molecular weight (Mn) of 100,000 to 500,000 as determined by GPC.

[0160] <(c2) Ingredient>

[0161] The component (c2) is a crosslinking agent, which is an organohydrogenpolysiloxane containing two or more hydrogen atoms (Si-H groups) bonded to silicon atoms in one molecule. The component (c2) has at least two, preferably 2 or more and 100 or less, and more preferably 3 or more and 50 or less hydrogen atoms (SiH groups) bonded to silicon atoms in one molecule, and a linear, branched, or cyclic organohydrogenpolysiloxane can be used.

[0162] The viscosity of the organohydrogenpolysiloxane of the component (c2) at 25° C. is preferably 1 to 5,000 mPa"s, more preferably 5 to 500 mPa"s. The organohydrogenpolysiloxane may be a mixture of two or more. The viscosity is measured using a rotational viscometer.

[0163] The (c2) component is blended so that the molar ratio of the Si-H group in the (c2) component to the alkenyl group in the (c1) component (Si-H group / alkenyl group) is in the range of 0.3 to 15, preferably 0.3 to 10, and particularly preferably 1 to 8. When the molar ratio of the SiH group to the alkenyl group is 0.3 or more, the crosslinking density will not be reduced, and problems such as the adhesive layer not curing will not occur, so it is preferred. If it is 15 or less, the crosslinking density will not be too high, and sufficient adhesion and tack can be obtained.

[0164] <(c3) Ingredient>

[0165] Component (c3) is a platinum catalyst (i.e., a platinum group metal catalyst), examples of which include chloroplatinic acid, an alcohol solution of chloroplatinic acid, a reaction product of chloroplatinic acid and an alcohol, a reaction product of chloroplatinic acid and an olefin compound, and a reaction product of chloroplatinic acid and a vinyl-containing siloxane.

[0166] The amount of component (c3) added is an effective amount, usually 1 to 5,000 ppm, preferably 5 to 2,000 ppm, based on the total amount of (c1) and (c2) as a platinum component (by mass). If it is 1 ppm or more, the curability of the composition will not decrease, the crosslinking density will not decrease, and the holding power will not decrease. If it is 5,000 ppm or less, the usable time of the treatment liquid can be extended.

[0167] The above-mentioned thermosetting siloxane polymer composition can be dissolved in a solvent to form a (C) layer solution, thereby used to form a temporary adhesive material layer. As a solvent, for example, hydrocarbon solvents such as pentane, hexane, cyclohexane, isooctane, nonane, decane, p-menane, pinene, isododecane, limonene, etc. are suitable for use; or volatile low molecular weight siloxanes such as hexamethyldisiloxane and octamethyltrisiloxane, which can be used alone or in combination of two or more. In addition, in order to improve heat resistance, a known antioxidant can be added to the thermosetting siloxane polymer composition. Further, it can also be filtered as needed. Then, the (C) layer is formed on the (B) layer in the same method as the (A) layer and the (B) layer, or after being coated on a protective film and removing the solvent, it is attached to the (B) layer, thereby forming a temporary adhesive material with a (C) layer.

[0168] At this time, the film thickness formed is preferably 0.1 to 30 μm, particularly preferably between 1.0 and 15 μm. If the film thickness is 0.1 μm or more, it is easier to peel off from a substrate or a support. On the other hand, if the film thickness is 30 μm or less, it can fully withstand the grinding process when forming a thin wafer. In addition, in order to further improve the heat resistance, a filler such as silica of less than 50 parts by mass can be added to the thermosetting siloxane polymer layer (C) relative to a total of 100 parts by mass of a mixture of the components (c1), (c2), and (c3) of the thermosetting siloxane polymer.

[0169] The (C) layer may be provided as an intermediate layer between the (A) layer and the (B) layer, or the (A) layer, the (B) layer, and the (C) layer may be provided in this order from the substrate side.

[0170] [Method for manufacturing substrate]

[0171] The laminate obtained through the above steps is further subjected to CVD processing or grinding and cutting processing, and then the substrate is peeled off from the support body, thereby obtaining a thin wafer.

[0172] The thickness of the obtained thin wafer is preferably typically 5 to 300 μm, more typically 10 to 100 μm.

[0173] That is, the present invention also provides a method for manufacturing a substrate. That is, a method for manufacturing a substrate, wherein, after obtaining a laminate by the method for manufacturing the laminate, a step (d) of processing the back side of the substrate is performed, and then, after a stripping step such as solution stripping or mechanical stripping, after further removing the support and the temporary adhesive material from the laminate, a step (e) of cleaning the substrate is performed, wherein the contact angle of water on the surface of the substrate from which the support is removed after cleaning is set to less than 30°. As the cleaning liquid used at this time, a cleaning liquid using a common organic solvent can be used.

[0174] The process (d) of processing the back side of the substrate is not particularly limited, and processes such as CVD processing or grinding and cutting can be listed. In the process (e), the above-mentioned method of removing the support body and temporary adhesive material from the laminate and the method of cleaning the substrate are not particularly limited, and known methods can be used. For example, as a method for removing the support body and temporary adhesive material, a method of peeling them off from the substrate can be listed, and as a method for cleaning the substrate, a method of spraying a washing solvent that can dissolve the residual temporary adhesive material, etc., and then further spraying an arbitrary solvent for rinsing can be listed.

[0175] In order to measure the water contact angle of the cleaned substrate, a known measurement method may be used. For example, the water contact angle of the substrate after the cleaning test can be measured using a contact angle meter DM-301 manufactured by Kyowa Interface Science, Inc.

[0176] According to the above-described method for manufacturing a substrate, it is possible to manufacture a substrate that does not cause problems due to a temporary adhesive material in a subsequent process and can easily manufacture a thin substrate having a through-hole electrode structure or a bump connection structure.

[0177] Example

[0178] The present invention is described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, parts in the following examples are parts by mass. In addition, Me represents a methyl group, and Vi represents a vinyl group.

[0179] [Resin solution preparation example 1]

[0180] 24 g of a thermoplastic resin, SPTON4033 (containing 30% styrene, manufactured by KURARAY CO., LTD.), which is a hydrogenated styrene-isoprene-butadiene copolymer, was dissolved in 176 g of isononane to obtain a 12% by mass hydrogenated styrene-isoprene-butadiene copolymer isononane solution. The obtained solution was filtered with a 0.2 μm membrane filter to obtain an isononane solution (A-1) of a thermoplastic resin.

[0181] [Resin solution preparation example 2]

[0182] 30 g of a thermoplastic resin, SPTON4044 (containing 32% styrene, manufactured by KURARAY CO., LTD.), which is a hydrogenated styrene-isoprene-butadiene copolymer, was dissolved in 176 g of isononane to obtain a 12% by mass hydrogenated styrene-isoprene-butadiene copolymer isononane solution. The obtained solution was filtered with a 0.2 μm membrane filter to obtain an isononane solution (A-2) of a thermoplastic resin.

[0183] [Resin solution preparation example 3]

[0184] In a flask equipped with a stirrer, a thermometer, a nitrogen replacement device and a reflux condenser, 43.1 g of 9,9'-bis(3-allyl-4-hydroxyphenyl)fluorene (M-1), 29.5 g of an organohydrogensiloxane represented by the average structural formula (M-3), 135 g of toluene, and 0.04 g of chloroplatinic acid were added, and the temperature was raised to 80°C. Then, 17.5 g of 1,4-bis(dimethylsilyl)benzene (M-5) was added dropwise to the flask over 1 hour. At this time, the temperature in the flask was raised to 85°C. After the addition was completed, the mixture was further aged at 80°C for 2 hours, toluene was distilled off, and 80 g of cyclohexanone was added at the same time to obtain a resin solution with a resin solid content concentration of 50% by mass and cyclohexanone as a solvent. When the molecular weight of the resin component of the solution was measured by GPC, the weight average molecular weight was 45,000 in terms of polystyrene. Furthermore, 7.5 g of EOCN-1020 (manufactured by Nippon Kayaku Co., Ltd.) as an epoxy crosslinking agent was added to 50 g of the resin solution, 0.2 g of BSDM (bis(tert-butylsulfonyl)diazomethane) manufactured by Wako Pure Chemical Industries, Ltd. as a curing catalyst was added, and 0.1 g of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate) (trade name: Adekastab AO-60) as an antioxidant was further added, and filtered with a 1 μm membrane filter to obtain a resin solution (B-1). The elastic modulus of the cured film obtained by curing the resin was 300 MPa at 25°C as measured by dynamic viscoelasticity measurement.

[0185] [Resin solution preparation example 4]

[0186] In a 5L flask equipped with a stirrer, a thermometer, a nitrogen replacement device and a reflux condenser, 84.1g of the epoxy compound (M-2) was dissolved in 600g of toluene, and then 294.6g of the compound (M-3) and 25.5g of the compound (M-4) were added and heated to 60°C. Then, 1g of a carbon-supported platinum catalyst (5% by mass) was added, and after confirming that the internal reaction temperature had risen to 65-67°C, it was further heated to 90°C and aged for 3 hours. After cooling to room temperature, 600g of methyl isobutyl ketone (MIBK) was added, and the reaction solution was pressure filtered using a filter to remove the platinum catalyst. The solvent in the resin solution was removed by reduced pressure distillation, and 270g of propylene glycol methyl ether acetate (PGMEA) was added at the same time to obtain a resin solution with a solid content concentration of 60% by mass and PGMEA as a solvent. When the molecular weight of the resin in the resin solution was measured by GPC, the weight average molecular weight was 28,000 in terms of polystyrene. Furthermore, 9 g of TEP-TPA (manufactured by Asahi Organic Chemicals Industry Co., Ltd.) as a tetrafunctional phenol compound and 0.2 g of tetrahydrophthalic anhydride (manufactured by New Japan Chemical Co., Ltd., Rikacid HH-A) were added to 100 g of the resin solution, and filtered with a 1 μm membrane filter to obtain a resin solution (B-2). The elastic modulus of the cured film formed by curing the resin measured by dynamic viscoelasticity measurement at 25° C. was 500 MPa.

[0187] [Chemical formula 14]

[0188]

[0189] [Resin solution preparation example 5]

[0190] To a solution consisting of 100 parts of polydimethylsiloxane and 400 parts of isododecane, 10 parts of an organohydrogen polysiloxane represented by the following formula (M-7) (2 mol relative to alkenyl) were added and mixed, wherein the polydimethylsiloxane had 3 mol% of vinyl groups at both ends and side chains, the molecular ends were capped with SiMe2Vi groups, and the number average molecular weight (Mn) obtained based on GPC was 50,000. Further, 0.05 parts of a platinum catalyst CAT-PL-5 (manufactured by Shin-Etsu Chemical Co., Ltd.) was added to 100 parts of the polydimethylsiloxane, and filtered with a 0.2 μm membrane filter to obtain a thermosetting siloxane polymer solution (C-1).

[0191] [Chemical formula 15]

[0192]

[0193] [Resin solution preparation example 6]

[0194] To a solution consisting of 100 parts of polydimethylsiloxane and 400 parts of isododecane, 5 parts of an organohydrogen polysiloxane represented by the following formula (M-6) (2 mol relative to alkenyl) were added and mixed, wherein the polydimethylsiloxane had 3 mol% of vinyl groups at both ends and side chains, the molecular ends were capped with SiMe2Vi groups, and the number average molecular weight (Mn) obtained based on GPC was 50,000. Further, 0.05 parts of a platinum catalyst CAT-PL-5 (manufactured by Shin-Etsu Chemical Co., Ltd.) was added to 100 parts of polydimethylsiloxane, and filtered with a 0.2 μm membrane filter to obtain a thermosetting siloxane polymer solution (C-2).

[0195] [Chemical formula 16]

[0196]

[0197] (Example 1)

[0198] The thermoplastic resin solution (A-1) was coated on a polyethylene terephthalate (PET) film (thickness 38 μm) as a release substrate at a coating speed of 0.4 m / min using a notch wheel coater as a coating machine, and dried to form a first temporary adhesive material layer (A-1) layer. The notch wheel coater was further used as a coating machine, and the resin solution (B-1) was coated on a polyethylene terephthalate (PET) film having the above-mentioned (A-1) layer formed thereon at a coating speed of 0.4 m / min, and dried to form a second temporary adhesive material layer (B-1) layer. Furthermore, the thermosetting siloxane polymer solution (C-1) was applied to a polyethylene terephthalate (PET) film having the (B-1) layer and the (A-1) layer at a coating speed of 0.4 m / min using a notch wheel coater as a coating machine, and dried to form a (C-1) layer as a third temporary adhesive material layer. Then, a polyethylene (PE) film (thickness 100 μm) was attached to the surface of the film as a protective film at a pressure of 1 MPa, and wound on a plastic tube at a speed of 0.4 m / min and a tension of 30 N to form a film roll with a diameter of 130 mm.

[0199] Step (a): Step of laminating a temporary adhesive material on the non-processed surface of a substrate or a support

[0200] A glass plate with a diameter of 200 mm (thickness: 500 μm) was used as a support, and a vacuum laminator TEAM-100 (manufactured by Takatori Corporation) was used. The vacuum degree in the vacuum chamber was set to 80 Pa. While peeling off the protective film from the temporary adhesive film roll for substrate processing, a composite film-like temporary adhesive material consisting of the (A-1) layer, the (B-1) layer and the (C-1) layer was stretched, and laminated in a manner such that the (C-1) layer was arranged on the support, and then the release substrate was removed.

[0201] Step (b): Preheating the substrate and the support before bonding

[0202] A silicon wafer (thickness: 725 μm) with a diameter of 200 mm and copper posts (copper posts) with a height of 40 μm and a diameter of 40 μm formed on the entire surface was used as a substrate. The substrate was preheated in a vacuum bonding device (EVG520IS) at the temperature listed in Table 1 in such a way that the copper post surface of the substrate was opposite to the temporary adhesive material layer of the support body produced in step (a).

[0203] Step (c): a step of bonding the substrate and the support body via a temporary adhesive material

[0204] In 10 -3 The substrate and the support configured in step (b) were bonded under a chamber pressure of less than 100 mbar and a load of 5 kN. The laminate was heated, bonded, and bonded at the temperature and time described in Table 1, and then heated in an oven at 180° C. for 1 hour to cure the (B-1) layer and the (C-1) layer to prepare a sample.

[0205] (Examples 2 to 5 and Comparative Examples 1 to 4)

[0206] The samples were prepared by treating in the same manner as in Example 1 under the conditions described in Table 1. In addition, in the temporary adhesive material column of Table 1, for example, "A-1 / B-1 / C-1" means that the temporary adhesive material is composed of (A-1) layer, (B-1) layer and (C-1) layer, and the (C-1) layer is arranged on the support.

[0207] Here, a glass plate is used as a support in order to visually determine abnormalities after bonding the substrates, but a light-impermeable silicon substrate such as a wafer may also be used.

[0208] The bonded substrates (samples) were subjected to the following tests, and the results of Examples and Comparative Examples are shown in Table 1. The evaluation was performed in the following order, and the subsequent evaluation was terminated at the time when the back grinding resistance test was judged as "x".

[0209] - Adhesion Test -

[0210] As described above, the laminate (sample) obtained by heat curing at 180° C. for 1 hour in an oven was cooled to room temperature, and the bonding condition of the interface was then confirmed with the naked eye. The situation where no abnormality such as blistering occurred on the interface was evaluated as good and indicated by “○”, and the situation where an abnormality occurred was evaluated as poor and indicated by “×”.

[0211] -Back grinding resistance test-

[0212] The backside of the silicon wafer was ground using a diamond grinding wheel on a grinder (manufactured by DISCO Corporation, DAG810) for the laminate (sample) obtained by heating and curing at 180°C for 1 hour in an oven as described above. After the final substrate thickness was ground to 50 μm, an optical microscope (100 times) was used to check for abnormalities such as cracks and peeling. The situation where no abnormality occurred was indicated as "○", and the situation where an abnormality occurred was indicated as "×".

[0213] -CVD tolerance test-

[0214] The processed body after back grinding of silicon wafer is introduced into CVD device, and the generation test of 2μm SiO2 film is carried out to observe whether there is any abnormal appearance at this time. The situation where no abnormal appearance occurs is represented as "○", and the situation where voids, wafer expansion, wafer damage, etc. occur is represented as "×". The conditions of CVD tolerance test are as follows.

[0215] Equipment name: Plasma CVD PD270STL (manufactured by Samco Inc.)

[0216] RF500W, internal pressure 40Pa

[0217] TEOS (tetraethoxysilane): O2 = 20 sccm: 680 sccm

[0218] -Peelability Test-

[0219] The peelability of the substrate is evaluated by the following method. First, a dicing tape is attached to the wafer side of the wafer processed body that has been thinned to 50μm after the CVD tolerance test using a dicing frame, and the dicing tape surface is placed on an adsorption plate by vacuum adsorption. Then, at room temperature, one point of the glass is lifted up using tweezers to peel off the glass substrate. The case where a 50μm wafer can be peeled off without causing cracks is indicated as "○", and the case where abnormalities such as cracks occur is evaluated as poor and indicated as "×".

[0220] -Cleaning Removability Test-

[0221] The 200 mm wafer (exposed to the CVD tolerance test conditions) mounted on the dicing frame via the dicing tape after the above-mentioned peelability test was placed on a spin coater, and after spraying isononane as a cleaning solvent for 3 minutes, the wafer was rotated while being rinsed by spraying isopropyl alcohol (IPA). Then, the appearance was observed and the presence of residual adhesive material resin was checked with the naked eye. The case where no resin residue was confirmed was evaluated as good and indicated by "○", and the case where the resin residue was confirmed was evaluated as poor and indicated by "×".

[0222] -Contact angle test-

[0223] The water contact angle of the wafer after the cleaning test was measured using the following apparatus. Table 1 shows the average value of the contact angle measured five times.

[0224] Measurement device: Contact angle meter DM-301 manufactured by Kyowa Interface Science, Inc.

[0225] -Determination of melt viscosity-

[0226] The rheometer (HAAKE MARS II (manufactured by EKO Instruments BV)) was used to measure the temperature in the range of 25°C to 200°C with a gap of 500 μm, a sample diameter of 8 mm, a heating rate of 10°C / min, and a frequency of 1 Hz. The melt viscosity ratio α / β of each layer is shown in Table 1.

[0227] [Table 1]

[0228] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Temporary bonding materials A-1 / B-1 / C-1 A-1 / B-2 / C-2 A-2 / B-1 / C-2 A-2 / B-2 / C-1 A-1 / B-1 / C-1 A-1 / B-1 / C-1 A-1 / B-1 / C-1 A-1 / B-1 / C-1 A-2 / B-1 / C-1 Substrate heating temperature 150℃ 120℃ 150℃ 200℃ 125℃ 70℃ 150℃ Not heated 180℃ Support heating temperature 100℃ 100℃ 70℃ 150℃ 110℃ 70℃ Not heated 100℃ 180℃ Joining time 1min 1min 1min 1min 1min 5min 5min 5min 1min Adhesion ○ ○ ○ ○ ○ × × × ○ Back grindability ○ ○ ○ ○ ○ × × × ○ CVD tolerance ○ ○ ○ ○ ○ - - - ○ Peelability ○ ○ ○ ○ ○ - - - ○ Cleaning Removability ○ ○ ○ ○ ○ - - - × Contact angle <10° <10° <10° <10° <10° - - - 45° Viscosity ratio (25℃) 0.2 0.1 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Viscosity ratio (minimum) 300 150 400 200 300 300 300 300 400

[0229] Viscosity ratio (25°C): Melt viscosity ratio at 25°C

[0230] Viscosity ratio (minimum): minimum melt viscosity ratio between 100°C and 200°C

[0231] As shown in Table 1, it can be seen that under the heating conditions before joining that meet the requirements of the present invention, the substrate and the support are easily temporarily bonded and easily peeled off, and in particular, the cleaning and removal properties are excellent (Examples 1 to 5). On the other hand, in Comparative Examples 1 to 4, where the heating conditions before joining do not meet the requirements of the present invention, there are problems in adhesion or cleaning and removal properties.

[0232] The present invention is not limited to the above-described embodiments. The above-described embodiments are merely examples, and any technical solution having substantially the same configuration as the technical concept described in the claims of the present invention and having the same function and effect is included in the technical scope of the present invention.

Claims

1. A method for manufacturing a laminated body, which is a method for manufacturing a laminated body by bonding a non-processed surface of a substrate to be processed on the back side and a support body via a temporary adhesive material, characterized in that: As the temporary adhesive material, a temporary adhesive material having at least two layers including a first temporary adhesive material layer (A) located on the substrate side and a second temporary adhesive material layer (B) located closer to the support body side than the first temporary adhesive material layer (A) is used, and the melt viscosity ratio α / β of the first temporary adhesive material layer (A) and the second temporary adhesive material layer (B) is 10 or less in terms of the melt viscosity ratio at 25° C. and 100 or more in terms of the minimum melt viscosity ratio at 100° C. to 200° C., The method for manufacturing the laminate comprises: A step (a) of laminating the temporary adhesive material on either or both of the non-processed surface of the substrate and the support; (b) preheating the substrate and the support before starting bonding; step (c) of bonding the substrate and the support body via the temporary adhesive material, In the step (b), the substrate is heated to a temperature of 50°C to 250°C, and the support is heated to a temperature of 50°C to 250°C and different from that of the substrate. At the same time, in the step (c), the bonding is started in a state where the temperature of the pre-heated substrate is different from that of the support.

2. The method for manufacturing a laminate according to claim 1, wherein: In the step (c), bonding is started in a state where the temperature of the substrate and the temperature of the support body differ by 10° C. or more.

3. The method for manufacturing a laminate according to claim 1, wherein: In the step (a), the first temporary adhesive material layer (A) and the second temporary adhesive material layer (B) are formed adjacent to each other and laminated.

4. The method for manufacturing a laminate according to claim 2, wherein: In the step (a), the first temporary adhesive material layer (A) and the second temporary adhesive material layer (B) are formed adjacent to each other and laminated.

5. The method for producing a laminate according to claim 1, wherein: The second temporary adhesive material layer (B) is composed of a thermosetting resin, and a temporary adhesive material is used in which the elastic modulus of a cured film obtained by curing the thermosetting resin measured by dynamic viscoelasticity measurement is 50 MPa to 1 GPa at 25°C.

6. The method for manufacturing a laminate according to claim 3, wherein: The second temporary adhesive material layer (B) is composed of a thermosetting resin, and a temporary adhesive material is used in which the elastic modulus of a cured film obtained by curing the thermosetting resin measured by dynamic viscoelasticity measurement is 50 MPa to 1 GPa at 25°C.

7. The method for manufacturing a laminate according to claim 1, wherein: The second temporary adhesive material layer (B) is formed of a thermosetting resin composition, wherein the thermosetting resin composition contains, as a crosslinking agent, 0.1 to 50 parts by weight of any one or more selected from the group consisting of an amino condensate modified with formalin or formalin-alcohol, a melamine resin, a urea-formaldehyde resin, a phenol compound having an average of 2 or more methylol or alkoxymethylol groups in one molecule, and an epoxy compound having an average of 2 or more epoxy groups in one molecule, relative to 100 parts by weight of a siloxane bond-containing polymer having a repeating unit represented by the following general formula (1) and a weight average molecular weight of 3,000 to 500,000. In the formula, R 1 ~R 4 represents a monovalent hydrocarbon group having 1 to 8 carbon atoms which may be the same or different; m is an integer of 1 to 100, B is a positive number, and A is 0 or a positive number; wherein A+B=1; X is a divalent organic group represented by the following general formula (2), In the formula, Z is a divalent organic group selected from any one of the following groups, N is 0 or 1; in addition, R 5 , R 6 are alkyl or alkoxy groups having 1 to 4 carbon atoms, which may be the same or different from each other; k is any one of 0, 1, and 2, 8. The method for producing a laminate according to claim 1, wherein: The second temporary adhesive material layer (B) is formed of a thermosetting resin composition, wherein the thermosetting resin composition contains 0.1 to 50 parts by weight of any one or more selected from a phenol compound having an average of 2 or more phenolic hydroxyl groups in one molecule and an epoxy compound having an average of 2 or more epoxy groups in one molecule as a crosslinking agent, relative to 100 parts by weight of a siloxane bond-containing polymer having a repeating unit represented by the following general formula (3) and a weight average molecular weight of 3,000 to 500,000. In the formula, R 7 ~R 10 represents a monovalent hydrocarbon group having 1 to 8 carbon atoms which may be the same or different; in addition, n is an integer of 1 to 100, D is a positive number, and C is 0 or a positive number; wherein C+D=1; further, Y is a divalent organic group represented by the following general formula (4), In the formula, V is a divalent organic group selected from any one of the following groups, and p is 0 or 1; in addition, R 11 , R 12 are alkyl or alkoxy groups having 1 to 4 carbon atoms, which may be the same or different from each other; h is any one of 0, 1, and 2, 9. The method for manufacturing a laminate according to claim 7, wherein: The second temporary adhesive material layer (B) is formed of a thermosetting resin composition, wherein the thermosetting resin composition contains 0.1 to 50 parts by weight of any one or more selected from a phenol compound having an average of 2 or more phenolic hydroxyl groups in one molecule and an epoxy compound having an average of 2 or more epoxy groups in one molecule as a crosslinking agent, relative to 100 parts by weight of a siloxane bond-containing polymer having a repeating unit represented by the following general formula (3) and a weight average molecular weight of 3,000 to 500,000. In the formula, R 7 ~R 10 represents a monovalent hydrocarbon group having 1 to 8 carbon atoms which may be the same or different; in addition, n is an integer of 1 to 100, D is a positive number, and C is 0 or a positive number; wherein C+D=1; further, Y is a divalent organic group represented by the following general formula (4), In the formula, V is a divalent organic group selected from any one of the following groups, and p is 0 or 1; in addition, R 11 , R 12 are alkyl or alkoxy groups having 1 to 4 carbon atoms, which may be the same or different from each other; h is any one of 0, 1, and 2, 10. A method for manufacturing a substrate, characterized in that: After obtaining the laminated body by the method for producing a laminated body according to any one of claims 1 to 9, a step (d) of processing the back side of the substrate is performed, and then after further removing the support body and the temporary adhesive material from the laminated body, a step (e) of washing the substrate is provided, In the step (e), the contact angle of water on the surface of the washed substrate from which the support has been removed is set to less than 30°.

Citation Information

Patent Citations

  • Charge transition type gas discharge panel

    JP1985059631A

  • Laminate including substrate to be ground, method of manufacturing the same, method of manufacturing ultrathin substrate using the laminate, and apparatus therefor

    JP2004064040A

  • Wafer processing bonding material, wafer laminate, and thin wafer manufacturing method

    CN106467715A

  • Wafer Processing Laminate And Method For Processing Wafer

    CN107039239A